Major Depressive Disorder as a Condition Negatively Impacting Both Mental and Physical Functioning. What to Do When There Is Treatment Resistance? - Monika Makar; Daria Michałka; Zuzanna Gałuszka; Natalie Papachristoforou; Justyna Głowacka; Aleksandra Kocjan; Emilia Bąk; Natalia Tekiela; Radosław Chmiel; Tomasz Bartuś (Quality in Sport)
The objective of this article is to assess the efficacy and safety of diverse therapeutic strategies for treatment-resistant depression (TRD), encompassing both pharmacological and non-pharmacological interventions. Additionally, the review identifies potential avenues for future research within this domain.